2012 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2012
DOI: 10.1109/embc.2012.6347311
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of novel, secure, real-time, portable ultrasound transmission from an austere international location

Abstract: There is not sufficient access to medical care or medical expertise in many parts of the world. An innovative telemedicine system has been developed to provide expert medical guidance to field caregivers [who have less medical expertise but can reach the patient population in need]. Real-time ultrasound video images have been securely transmitted from the Dominican Republic to Hackensack University Medical Center, Hackensack NJ (HackensackUMC), while the expert physician at HackensackUMC maintained direct voic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Three prototype medical units and support vehicles were designed and built collaborating with vehicle manufacturers. There were also various research efforts related to the fleet development [1,2].…”
Section: Methodsmentioning
confidence: 99%
“…Three prototype medical units and support vehicles were designed and built collaborating with vehicle manufacturers. There were also various research efforts related to the fleet development [1,2].…”
Section: Methodsmentioning
confidence: 99%
“…As noted previously, rural health care centres often lack the radiology specialist or trained obstetricians needed to register their own ultrasound machine/s. With the increasing connectivity of rural India and the safe, private transferring of ultrasound images from even remote locations (62), the PCPNDT law could be modified to reward collaboration as a means to improving care in rural India. The first step in this process would be to allow radiologists to register additional machines at facilities where they are not physically present (ideally in areas with large unmet healthcare needs) if each radiologist can demonstrate ongoing, meaningful work with the rural clinic or hospital that now has an ultrasound machine.…”
Section: Possible Solutionsmentioning
confidence: 99%
“…This was feasible with the help of different secure cellular and satellite networks from an austere environment. [ 45 ] Portable ultrasonography utility has extended to diagnosing fractures in austere combat environments. A prospective study showed that the use of portable US by certified emergency physicians on patients presenting with acute closed fractures assisted in field triage: cases where a fracture or cortical irregularity was detected on US were triaged to an appropriate facility with radiographic capabilities.…”
Section: B Ody Of M Anuscriptmentioning
confidence: 99%